Sustained Response to Targeted Therapy in a Patient With Disseminated Anaplastic Pleomorphic Xanthoastrocytoma. Issue 6 (August 2018) - Amayiri, Nisreen; Swaidan, Maisa; Al-Hussaini, Maysa; Halalsheh, Hadeel; Al-Nassan, Anwar; Musharbash, Awni; Tabori, Uri; Hawkins, Cynthia; Bouffet, Eric
Abstract : Pleomorphic xanthoastrocytoma is a rare brain tumor with unique high frequency of BRAF V600E mutation which is plausible for targeted therapy. The anaplastic variant has generally worse prognosis. We present an adolescent patient with a disseminated relapse of anaplastic pleomorphic xanthoastrocytoma following surgery, radiotherapy, and chemotherapy. She had a dramatic and prolonged response to a BRAF inhibitor (Dabrafinib) and later to addition of a MEK inhibitor (Trametinib) on tumor progression. With minimal side effects and a good quality of life, the patient is alive more than 2 years after initiation of targeted therapy. This experience confirms the potential role of targeted treatments in high-grade BRAF-mutated brain tumors.